THE IMPLEMENTATION OF MANAGEMENT CLASS IN KINDERGARTEN AT AL ARABI - Armanila, Armanila; Harahap, Hotni Sari; Husna, Zuriatul (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The purpose of the study was to find out about the implementation of classroom management in Al Farabi Islamic Kindergarten in the management of classroom management. The research method used is descriptive qualitative with data collection techniques in the form of interview, observation, and documentation instruments, while the data analysis uses data reduction, data display, and conclusion drawing data. The results show that Al Farabi Integrated Islamic Kindergarten has paid attention to classroom management which includes structuring infrastructure according to learning activities, designing classes, getting sunlight into the classroom, providing trash cans in the classroom, a place to play and learn in the classroom. classrooms, colorful tables and chairs, adding accessories to the classroom, by paying attention to this, the process and learning objectives will go according to plan, because the teacher can create an effective and fun learning atmosphere, because good class management is a class that can optimize early childhood development. This research is expected to contribute to creating good classroom management in Integrated Islamic Kindergartens of its kind.